2016
DOI: 10.1016/j.ymeth.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Bioinformatics

Abstract: Recent technological advances allow for high throughput profiling of biological systems in a cost-efficient manner. The low cost of data generation is leading us to the “big data” era. The availability of big data provides unprecedented opportunities but also raises new challenges for data mining and analysis. In this review, we introduce key concepts in the analysis of big data, including both “machine learning” algorithms as well as “unsupervised” and “supervised” examples of each. We note packages for the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The term "Big Data" refers to the recording and analysis of data sets which are so large, multidimensional, diverse, and complex that traditional software solutions are not adequate to process them [68]. The advent of Big Data is the result of the development of novel technologies that surpass the capacity of paper-based information management [69].…”
Section: Big Datamentioning
confidence: 99%
“…The term "Big Data" refers to the recording and analysis of data sets which are so large, multidimensional, diverse, and complex that traditional software solutions are not adequate to process them [68]. The advent of Big Data is the result of the development of novel technologies that surpass the capacity of paper-based information management [69].…”
Section: Big Datamentioning
confidence: 99%
“…Based on R software, we performed classification, regression, clustering, dimension-reduction, model selection, statistical analysis, and data preprocessing, which can quickly complete the entire process of ML ( 27 ). In the present study, we considered patients whose mp-MRI examination indicated PI-RADS v2 4/5 score and used ImageJ and other software to extract the TF of all lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The intragroup data repeatability of each group was verified by Pearson's correlation. R programming language provides operating environment and software for drawing of graphs and statistical analysis [ 15 ]. Use heatmaps to visualize correlations between samples in the same dataset and using R to draw the heatmap.…”
Section: Methodsmentioning
confidence: 99%